2016
DOI: 10.1016/j.bbr.2015.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the performance of NK1R−/− (‘knockout’) and wildtype mice in the 5‑Choice Continuous Performance Test

Abstract: HighlightsWe compared the behaviour of NK1R−/− mice and wildtypes in the 5-Choice Continuous Performance Test.NK1R−/− mice did not express excess impulsivity (premature response or false alarms) in this test.NK1R−/− mice expressed excessive perseveration, which is common in ADHD.The findings point to a behavioural phenotype for ADHD patients with polymorphism of the TACR1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 73 publications
1
25
0
Order By: Relevance
“…Bars show mean±standard error of the mean (SEM) score for the five test conditions. White bars: wild types; shaded bars: NK1R-/- mice; NI-2: no-injection (results for NI-1 are reported in Porter et al, 2016); VEH: vehicle; MPH3, MPH10 and MPH30: methylphenidate 3, 10 and 30 mg/kg, respectively. Lines linking pairs of data indicate a statistically significant difference between the two genotypes at p <0.05 at least.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bars show mean±standard error of the mean (SEM) score for the five test conditions. White bars: wild types; shaded bars: NK1R-/- mice; NI-2: no-injection (results for NI-1 are reported in Porter et al, 2016); VEH: vehicle; MPH3, MPH10 and MPH30: methylphenidate 3, 10 and 30 mg/kg, respectively. Lines linking pairs of data indicate a statistically significant difference between the two genotypes at p <0.05 at least.…”
Section: Resultsmentioning
confidence: 99%
“…The protocol for training mice in the 5C-CPT is explained fully elsewhere (Porter et al, 2016; Young et al, 2009), but essential elements of the procedure are reported below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations